Análisis De La Percepción De La Tutoría En Los Alumnos De Primer Año De La Licenciatura En Gastronomía Del Instituto Tecnológico Superior De Escárcega - Ramírez, Ludwin Jaime Estrada; Moreno, Paula Viveros; Camal, María del Carmen Gómez; Espinosa, Jocabeth Eunice Naal (European Scientific Journal, ESJ, 2017)
The implementation of mentoring programs in higher level institutions has brought with it a series of implications that are susceptible to be evaluated, but above all, the way in which it is applied, and is generating the expected results for each student in the course The first semester and at the same time participates in the tutoring program corresponding to the Bachelor’s Degree in Gastronomy of the Instituto Tecnológico Superior de Escárcega. For this reason, the main objective of this basic research, of descriptive type, was to analyze the conceptualization of the tutoring processes that receive the students that were object of study. To achieve the objective, a questionnaire applied to the 64 tutors was used and validated using the Cronbach alpha coefficient, showing a value of 6,779, indicating that this instrument has an acceptable degree of reliability, validating its use for the collection of plotted data In the Excel 2010 program. The results indicated that 80% of the students surveyed disagree with the tutorial action processes they receive from their tutors, while only 20% reported the existence of certain tutorial activities. Therefore it should be considered in detail the assignment and personal relationship between the student and the assigned tutor, seeking the correct planning and development of the activities according to the Degree in the work plan based on the institutional program of tutoring of the Institutes Decentralized Technology.